MENINGKATKAN KEMAMPUAN DALAM MENYUSUN PARAGRAF DARI KALIMAT YANG DIACAK PADA MURID KELAS IV SDN 182 PALEMBANG - Fatimatuzzahra; Idawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem examined in this study is whether the guided exercise method users can improve the ability to compose paragraphs from scrambled sentences by the fourth grade students of SDN 182 Palembang through the guided exercise method. This type of research is classroom action research. The target consists of 4 components, namely (1) action planning, (2) action implementation, (3) observation, (4) reflection. The type of data used is qualitative data. The method used in this research is observation and interview methods. The observation method was used to identify and describe the implementation of improving the ability to compose paragraphs from sentences randomized by fourth grade students at SDN 182 Palembang. The interview method was used to obtain data that was not observed or not recorded during observation. Data analysis in this study used qualitative data analysis procedures. Based on these results, it can be concluded that applying the guided exercise method can improve the ability to compose paragraphs from scrambled sentences for fourth grade students of SDN 182 Palembang.   Keywords: compose, paragraphs, scrambled